2015
DOI: 10.1007/s00134-015-4041-5
|View full text |Cite
|
Sign up to set email alerts
|

Acute heart failure and cardiogenic shock: a multidisciplinary practical guidance

Abstract: A multidisciplinary approach along the entire patient journey from pre-hospital care to hospital discharge is needed to ensure early recognition, risk stratification, and the benefit of available therapies. Medical management should be planned according to the underlying mechanisms of various clinical scenarios of AHF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
119
0
10

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(130 citation statements)
references
References 100 publications
1
119
0
10
Order By: Relevance
“…Mechanical circulatory support may be necessary to prevent irreversible end-organ damage in cardiogenic shock (CS) [1,2]. For more than 40 years, the intra-aortic balloon pump (IABP) has been used in CS to improve coronary and peripheral perfusion via diastolic balloon inflation and to augment left ventricular (LV) performance via systolic balloon deflation through a decreased afterload [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Mechanical circulatory support may be necessary to prevent irreversible end-organ damage in cardiogenic shock (CS) [1,2]. For more than 40 years, the intra-aortic balloon pump (IABP) has been used in CS to improve coronary and peripheral perfusion via diastolic balloon inflation and to augment left ventricular (LV) performance via systolic balloon deflation through a decreased afterload [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the sickest patients were excluded in this trial [44]. For daily practice it is of utmost interest to know which vasopressor, inotrope, vasodilator or any combination is indicated for which patient and at what target [56, 57]. We found that for milrinone and levosimendan for critically ill adult patients with cardiac dysfunction evidence from trials with low risk of bias and low risk of random error is lacking to support its use [58].…”
Section: Discussionmentioning
confidence: 99%
“…The routine AHF management includes 12‐lead electrocardiogram (ECG) recording, vital sign monitoring, option for treatment with supplementary oxygen, non‐invasive ventilation (NIV), and administration of IV diuretics and vasodilators . However, the administration of pre‐hospital medication seems scarce .…”
Section: Introductionmentioning
confidence: 99%